The effect of an extended culture period on birth weight among singletons born after single or double vitrified embryo transfer - Wang, Ningling; Lin, Kaibo; Zhao, Xinxi; Zhang, Ping (Frontiers in Endocrinology, 2024)
Aim: To evaluate the effect of an extended culture period on birth weight among singletons born after vitrified-warmed embryo transfer.Methods: A retrospective cohort study was performed among 12400 women who gave birth to 1015, 1027, 687, and 9671 singletons after single blastocyst transfer, single cleavage-stage embryo transfer, double blastocyst transfer, and double cleavage-stage embryo transfer, respectively.The unadjusted birth weight of singletons born after vitrified blastocyst transfer were heavier than those born after cleavage-stage transfer (β=30.28, SE=13.17, P=0.022), as were the adjusted birth weights (β=0.09, SE=0.03, P=0.007).In addition, there was a 37% increased odd of having an infant with high birth weight after vitrified blastocyst transfer compared with vitrified cleavage stage transfer (OR=1.37, 95% CI:1.07-1.77).The unadjusted and adjusted birth weight and odds of having an infant with high birth weight significantly increased after blastocyst transfer compared with cleavage-stage embryo transfer in vitrified-warmed cycles.